2005
DOI: 10.2320/matertrans.46.1485
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cu Substitution on Thermoelectric Properties of Ge Clathrates

Abstract: We have prepared polycrystalline n-type Ba 8 Cu x Ga y Ge 46ÀxÀy (x ¼ 0{5, y ¼ 16 À 3x) clathrate compounds by arc melting and spark plasma sintering techniques and investigated the effect of Cu substitution for Ge on their thermoelectric properties. The Hall carrier concentration for Cu-substituted compounds is almost constant at the order of 10 20 cm À3 , which is comparable to that for Ba 8 Ga 16 Ge 30 stoichiometric compounds. The Seebeck coefficient for these compounds is comparable to that for n-Ba 8 Ga … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
31
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 7 publications
7
31
0
Order By: Relevance
“…The discrepancy between the nominal composition and the electronic properties is a known issue in Ge clathrates. 31 In the case of Ni-containing clathrate, Johnsen et al 30 suggested formation of vacancies as a possible explanation for this disagreement, and this seems to be a reasonable explanation for the variations observed in our samples as well.…”
Section: Electronic Propertiesmentioning
confidence: 64%
“…The discrepancy between the nominal composition and the electronic properties is a known issue in Ge clathrates. 31 In the case of Ni-containing clathrate, Johnsen et al 30 suggested formation of vacancies as a possible explanation for this disagreement, and this seems to be a reasonable explanation for the variations observed in our samples as well.…”
Section: Electronic Propertiesmentioning
confidence: 64%
“…8,11,13,14 The weighted mobilities of the K x Ba 8Àx Zn y Ge 46Ày samples were not as large as those of the related clathrates, but the K 8 Zn 4 Ge 42 sample showed a relatively large value as a result of its larger effective mass. To sum up so far, we could not obtain increases in mobility and in weighted mobility for K x Ba 8Àx Zn y Ge 46Ày , including K 4 Ba 4 Zn 6 Ge 40 with a highly ordered framework.…”
Section: -4mentioning
confidence: 91%
“…1). [18][19][20][21][22][23][24][25][26] 13 where the observed increases in mobility were mainly as a result of a decrease in the number of substituting atoms. Johnsen et al characterized several Ba 8 Ni 6Àx Ge 40þx (0 x 0.6) samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7][8][9][10][11][12][13] Anno et al 4,5,7,8) systematically investigated the thermoelectric properties of Ge clathrate compounds containing the transition elements (Cu, Ag, Au, Pd, Pt) in host. They have found that the Seebeck coefficient is enhanced due to the increased effective mass by Ag, Au, Pd, and Pt substitution.…”
Section: Introductionmentioning
confidence: 99%